2018
DOI: 10.1186/s12882-018-0967-5
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of tacrolimus combined with Tripterygium wilfordii polyglycoside for treating idiopathic membranous nephropathy

Abstract: BackgroundIdiopathic membranous nephropathy (IMN) is one of the most common adult nephrotic syndromes. Some patients with this disorder require immunosuppressive therapy. This retrospective case series was performed to assess the effects of tacrolimus (TAC) combined with Tripterygium wilfordii polyglycoside (TWG) in treating IMN.MethodsFrom January 2015 to August 2016, kidney-biopsy-proven IMN patients treated with TAC in the Chinese PLA General Hospital were screened. Data were retrieved from the patients’ me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Shang et al. conducted a retrospective study showed that TWG combined with tacrolimus resulted in a higher remission rate (85.7%) and lower relapse rate for treating PMN than tacrolimus combined with methylprednisolone group [ 9 ]. Furthermore, a randomized control trial reported that the remission rate is 86.9% in the TWG combined with prednisone group, similar to the tacrolimus combined with prednisone group, in treating PMN [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shang et al. conducted a retrospective study showed that TWG combined with tacrolimus resulted in a higher remission rate (85.7%) and lower relapse rate for treating PMN than tacrolimus combined with methylprednisolone group [ 9 ]. Furthermore, a randomized control trial reported that the remission rate is 86.9% in the TWG combined with prednisone group, similar to the tacrolimus combined with prednisone group, in treating PMN [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous Chinese patients with immunoglobulin A nephropathy (IgAN) and Henoch-Schonlein purpura nephritis have benefited from TWG since Leishi first proposed the usage of TWG in 1977 [ 6 , 7 ]. More encouragingly, in recent years, studies have shown that TWG combined with corticosteroid or tacrolimus therapy was effective for patients with nephrotic PMN [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the included studies of Shang Shunlai and Zhang Xiaojuan, after TAC monotherapy or combination therapy, the TR at the tenth to twelfth month was higher than the TR at the sixth month. [ 15 , 17 ] However, TAC monotherapy had similar TR compared with TAC-corticosteroid combination therapy at the tenth to twelfth month. [ 15 , 17 ] More studies are needed to prove that TAC-corticosteroid combination therapy may have stronger immunosuppressive effects than TAC monotherapy for IMN.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of rheumatoid arthritis, some of the western medicines compatible with T. wilfordii Hook F. are methotrexate, leflunomide, and etanercept (He et al, 2014;Zhou et al, 2018). In addition, the combination of tripterysium glycoside tablets with calcium dobesilate dispersible tablets or methylprednisolone is used clinically to treat nephrotic syndrome, and adverse reactions caused by this treatment are relatively slight (Shang et al, 2018). Traditional single drug compatibility and compound drug compatibility have the disadvantages of complex ingredients, low effective content, and uncontrollable quality.…”
Section: Prevention Strategiesmentioning
confidence: 99%